La educación; un pilar para el éxito de la mujer en la sociedad peruana - Mendoza Carrasco, Mariella Victoria (2012)
The woman in the XXI century longs andaspires to develop in a context whit equalopportunities, able to decide freely andexpress its thinking with sustenance andlogic, transforming the structures that stillaway from a place with equity within theeducational area, and play a significantrole in society with professional successand integral human development.